ALAT PENDETEKSI KONDISI TELUR DAN PENSORTIR BESAR TELUR AYAM BERBASIS ARDUINO UNO - Muhamad Fadil; Abdul Jabbar Lubis; Imran Lubis (STMIK KAPUTAMA, 2021)
Chicken egg farmers really need a long time to check the condition of good chicken eggs and sort the egg sizes for eggs to be sold. The design of an egg condition detector uses an LDR sensor composed of a 3 watt led as a light source and to measure the egg size using an ultrasonic sensor, a DC motor as a driving force, and the Arduino Uno. Arduino as an output signal processor for a series of sensors and a DC motor controller via the L293D driver IC. Based on the results of the study, it can be concluded that the device designed can determine the good and rotten condition of the eggs by displaying the writing on the 16x2 LCD and the buzzer will sound when the eggs are detected in a rotten condition. And the ultrasonic sensor checks the size of the egg where the size of the egg is measured in three types, namely large, medium and small.